Accurate and Cost‐Efficient Whole Genome Sequencing of Hepatitis B Virus Using Nanopore - Stenbäck, Joakim B.; Schmidt, Daniel; Noborg, Ulrika; Gustafsson, Joel; Norberg, Peter; Andersson, Maria E.; Fu, Michael X; Harvala, Heli; Ringlander, Johan (Journal of medical virology, 2025)
ABSTRACT Deep sequencing of the whole hepatitis B virus genome increases the analytical resolution and has the potential to improve molecular epidemiology investigations. The aim of this study was to develop and evaluate the performance of such deep sequencing using the Nanopore technology. The method includes an initial PCR step to generate two overlapping amplicons that cover the whole relaxed circular HBV genome found in circulating viral particles and covalently closed circular DNA in infected hepatocytes, followed by sequencing using the Nanopore rapid barcoding kit that allows parallel analysis of several samples in one reaction. The libraries can be sequenced with the standard Nanopore flow cell on MiniIon or GridIon devices, as well as the Flongle. The performance of the method was evaluated by comparing Nanopore and Sanger sequences or qPCR results from 64 clinical samples. The Nanopore‐derived consensus sequences were, on average, 99.9% similar to those from Sanger sequencing, and the full HBV genome was determined in samples with HBV DNA levels of approximately 3 log10 IU/mL with MagNA pure 96 extraction and < 2 log10 IU/mL using a high‐volume manual extraction protocol on a subset of samples from patients with very low viral load (1.62−3.74 IU/mL). A perfect agreement with Sanger/qPCR‐derived genotype was seen. The cost of sequencing per genome using the Nanopore method is low, ranging from 6 to 37 euros. We conclude that whole genome sequencing of HBV with Nanopore is well suited for genomic characterization, antiviral resistance mutation analysis, and genotyping of HBV in a routine laboratory setting.